A Synthetic, Small, Sulfated Agent Is a Promising Inhibitor of Chlamydia spp. Infection in vivo - Gallegos, Karen M.; Taylor, Christopher R.; Rabulinski, Daniel J.; Del Toro, Rosalinda; Girgis, Danielle E.; Jourha, Dapinder; Tiwari, Vaibhav; Desai, Umesh R.; Ramsey, Kyle H. (Frontiers in Microbiology, 2019)
Chlamydia is the most frequently reported sexually transmitted bacteria causing 2.9 million infections annually in the United States. Diagnosis, treatment, and sequelae of chlamydial disease cost billions of dollars each year in the United States alone. Considering that a heparin sulfate-like cell surface receptor is involved in Chlamydia infections, we reasoned that sulfated and sulfonated mimics of heparin sulfate would be useful in topical prophylactic prevention of Chlamydia. In this study, we tested a small, synthetic sulfated agent sulfated pentagalloyl glucoside (SPGG) and three synthetic sulfonated polymers PSS and SPS with average molecular weight in the range of 11 to 1000 kDa for inhibition against Chlamydia. Infection of HeLa cells with C. muridarum or C. trachomatis in the presence of increasing concentrations of SPGG or sulfonated polymers were quantified by immunofluorescence of Chlamydia inclusions. To determine whether in vitro pre-treatment of SPGG inhibits infection of C. muridarum, HeLa monolayers were incubated with SPGG-containing media, and then infected with Chlamydia. Our in vitro results show that SPGG pre-treatment inhibits Chlamydia infection in a dose-dependent manner. In addition, we further determined if SPGG treatment has an inhibitory effect during infection, therefore cell monolayers were infected with C. muridarum in the concurrent presence of SPGG. Our results show that SPGG inhibits C. muridarum infection with an IC50 at 10 μg/ml levels. We also tested the inhibitory effect of synthetic polymers PSS and SPS against Chlamydia and found inhibition of C. muridarum and C. trachomatis infections with IC50 ranging from 0.3 to 0.8 μg/ml. SPGG, PSS, and SPS inhibit formation of Chlamydia inclusions in a concentration-dependent manner. For evaluation of in vivo efficacy of the most effective agent in blocking C. muridarum, SPGG, we intravaginally pre-treated mice with SPGG before infection with C. muridarum. Cervical swabs were collected post-infection to quantify Chlamydia inclusions in vitro. Our in vivo data show that the SPGG-treated group has a statistically significant reduction of infection compared to the no-treatment control. Overall, our results show that SPGG could serve as a promising topical inhibitor for preventing Chlamydia infection.